Analisis Perbandingan Biaya dan Waktu Rigid Pavement antara Cast In Situ dengan Precast Menggunakan Metode AHP pada Proyek Peningkatan Ruas Jalan Banyakan - Tiron, Kabupaten Kediri, Jawa Timur - Ardiansyah, Ilmam; Beatrix, Michella (Politeknik Negeri Lhokseumawe, 2024)
The development of infrastructure in land transportation, namely roads, is one of the supports for economic growth in Indonesia. Road Functional Worthiness is the condition of a road section that meets the technical requirements for suitability to provide security and safety for its users as well as administrative requirements that provide legal certainty for Road Operators and Road users so that the Road can be operated for the public. The Banyakan – Tiron section is a road section in the district Kediri is the access road for Dhoho International Airport, Kediri. This research aims to determine the type of pavement that is more efficient and effective in the continuation of the Banyakan - Tiron road improvement project by comparing in terms of cost and time between the Precast Prestress Concrete Pavement (PPCP) method and the Cast in Situ method. The results of the analysis using the AHP method were obtained in terms of costs, according to respondents who preferred the Cast in Situ (CiS) method with a percentage of 80% and the CiS cost was IDR 7,693,476,000.00, while for Precast Prestress Concrete Pavement (PPCP) it was 20% with a cost of Rp. 9,292,262,000.00, Meanwhile, in terms of time between Conventional and Precast Prestress Concrete Pavement (PPCP), it is concluded that the PPCP implementation time is shorter than CiS with a percentage of 62% for PPCP and 38% for CiS from the calculation that PPCP implementation takes 29 days faster than CiS with 106 days while CiS takes 135 days.